Dating the bridge at Avignon (south France) and reconstructing the Rhone River fluvial palaeo-landscape in Provence from medieval to modern times. (December 2015) - Ghilardi, Matthieu; Sanderson, David; Kinnaird, Tim; Bicket, Andrew; Balossino, Simone; Parisot, Jean-Claude; Hermitte, Daniel; Guibal, Frédéric; Fleury, Jules T.
Abstract: This paper aims to date the construction and demise of the medieval bridge at Avignon by integrating sedimentological and stratigraphic evidence with geophysical surveys (ERT), optically stimulated luminescence (OSL) and radiocarbon chronologies. In this way the palaeo-environments of Barthelasse Island (Avignon) and the Labadie Plain (Villeneuve-les-Avignon) have been reconstructed, and the physical evidence of this iconic landscape placed in temporal and historic frameworks. In the course of this work the location of piers 9 and 10 (partly destroyed and buried today beneath sediments) of the former masonry bridge were re-discovered and cored to ca. 7 m depth. 14 C dating of large fragments of wood ( Abies Alba Mill.), from the pier settings, provides the first direct age determination (1213–1280 and 1238–1301 cal. AD) of the constructional phases for the stone bridge at 1250 ± 30 AD and reveals an allochtonous origin of the timber (fir tree) used to support it. This new date from a primary context post-dates the historical attribution based on the Benezet legend (dated to 1177–1185 cal. AD). These results suggest that the material associates with a rebuilding phase, potentially between AD 1234–1237, following the destructive activities of the French Army of Louis VIII during the siege of Avignon in AD 1226. Additionally, the integration of sedimentological data, OSL sediment dating, and 14 C results reveal that major detrital phases overlie the bedrock followed by rapid accretion of ca 3 to 7 m of sand to around 1650 ± 50 AD. This relates to the later stages of the Little Ice Age which are characterised by repeated floods and high sedimentation rates in the Lower Rhone River. In this period, the sedimentary archives and chronology record evidence of major environmental change, coincident with the political and economic conditions during the reign of French King Louis XIV and with the final demise of the medieval bridge across the Rhone at Avignon. Highlights: Foundations of the bridge at Avignon are made with wooden pillars (fir tree). The bridge at Avignon made with masonry is dated from AD 1250 ± 30. The bridge at Avignon made with stones cannot be attributed to the Saint Benezet legend (1177–1185). A phase of high sand deposition (3 to 7 m) has been dated with OSL around the mid 17th Cent. AD. Rhone valley floor at Avignon was at + 14 m amsl during Roman times and is at + 17 m amsl after LIA.